2020
DOI: 10.5152/j.aott.2020.20166
|View full text |Cite
|
Sign up to set email alerts
|

The management of orthopedics and traumatology patients during SARS-CoV-2 pandemic

Abstract: Relationship between the tilt angle of bipolar radial head prostheses and radiological radiocapitellar instability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Nevertheless, in many circumstances, the lack of precision in stratifying activity led to unforeseen challenges [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Having to abruptly adopt a paradigm shift and decide what defined an emergency and who required mandatory surgical treatment meant many cases were treated conservatively or postponed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, in many circumstances, the lack of precision in stratifying activity led to unforeseen challenges [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Having to abruptly adopt a paradigm shift and decide what defined an emergency and who required mandatory surgical treatment meant many cases were treated conservatively or postponed.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic procedures and elective joint replacements were also drastically reduced during the ‘lockdown’ period in Austria, Germany, Greece, and Switzerland, while trauma cases reduced to up to one third of the pre-pandemic levels [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Turgut et al reported that in Turkey, fractures decreased by approximately one third during the ‘lockdown’ period compared with previous two years, most likely due to less mobility on the streets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations